Larger Elm Leaf Beetle, Monocesta coryli (Say) (Insecta: Coleoptea: Chrysomelidae) - Michael C. Thomas (EDIS)
The larger elm leaf beetle, Monocesta coryli (Say), is one of the most conspicuous members of Florida's leaf beetle fauna. Although usually uncommonly collected in this state, it occasionally is abundant enough to cause defoliation of both native and exotic elms (Ulmus spp.) in ornamental and natural settings. This document is EENY-180 (originally published as DPI Entomology Circular 370), one of the Featured Creatures series of the Entomology and Nematology Department, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2000.